2013
DOI: 10.1111/1751-7915.12059
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation: a genuine technology to remediate radionuclides from the environment

Abstract: SummaryRadionuclides in the environment are a major human and environmental health concern. Like the Chernobyl disaster of 1986, the Fukushima Daiichi nuclear disaster in 2011 is once again causing damage to the environment: a large quantity of radioactive waste is being generated and dumped into the environment, and if the general population is exposed to it, may cause serious life-threatening disorders. Bioremediation has been viewed as the ecologically responsible alternative to environmentally destructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(50 citation statements)
references
References 92 publications
0
48
0
2
Order By: Relevance
“…Stimulation of the subsurface to promote metal reduction has been proposed for the treatment of 99 Tc contaminated groundwater, and soluble Tc(VII) has been shown to be immobilised as poorly soluble Tc(IV) under Fe(III)-reducing conditions (Icenhower et al 2010;Lloyd et al 2000;Newsome et al 2014;Prakash et al 2013). During bioreduction, the addition of an electron donor, for example acetate, promotes microbial respiration and a cascade of terminal electron accepting process develop as the bacteria couple the oxidation of the electron donor to the reduction of available electron acceptors in the subsurface in the order oxygen > nitrate > manganese > iron > sulfate > methane.…”
Section: Mmentioning
confidence: 99%
“…Stimulation of the subsurface to promote metal reduction has been proposed for the treatment of 99 Tc contaminated groundwater, and soluble Tc(VII) has been shown to be immobilised as poorly soluble Tc(IV) under Fe(III)-reducing conditions (Icenhower et al 2010;Lloyd et al 2000;Newsome et al 2014;Prakash et al 2013). During bioreduction, the addition of an electron donor, for example acetate, promotes microbial respiration and a cascade of terminal electron accepting process develop as the bacteria couple the oxidation of the electron donor to the reduction of available electron acceptors in the subsurface in the order oxygen > nitrate > manganese > iron > sulfate > methane.…”
Section: Mmentioning
confidence: 99%
“…The tight homeostatic control mechanisms, which could limit metal influx or efflux of accumulated metals inside the cell, can be used for the improvement of bioremediation systems to remove or reduce the concentration of radionuclides from spent decontamination solutions (Liu and Duu-Jong 2014;Won et al 2014). Recent developments in microbiology and molecular biology have been applied for metal bioremediation through construction of bioengineered microorganisms (Gadd and White 1989;Daly 2000;Gunjan et al 2005;Lloyd and Renshaw 2005;Kumar et al 2007;Prakash et al 2013;Shih and Shen-Long 2014). Recently, the extremely radioresistant bacteria such as Deinococcus geothermalis and D. radiodurans have been bioengineered to reduce the organic solvents and uranium from nuclear waste (Lange et al 1998;Appukuttan et al 2006;Kulkarni et al 2013;Misra et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates an inefficient use of large amount of cation-exchange resin. The large amount of solid radioactive waste thus generated also requires prolonged safe storage (for tens of years) in tile holes/trenches (Venkateswaran et al 2003;Prakash et al 2013;Frišták et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity of radioactive compound is furthermost environmental anxiety which poses a major concern for health issue and is serious threat for life. Various studies revealed a lethal effect on human health due to direct contact, including the risk of leukaemia, leucopenia, kidney damage, and even genetic disorders (Prakash et al 2013). While indirect transmission of this toxic radionuclide via food chain also causes serious health hazards.…”
Section: Bioremediation Of Radioactive Compoundsmentioning
confidence: 99%